(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2006)
The influence of sludge on the groundwater’s quality has been shown on the bases of the agricultural exploitation of the sludge from a sewage-treatment plant. Little thickness of unsaturated zone (8.8 m) is not effective protection against the infiltration of the pollution from the surface. Unsaturated zone consist of sand of permeability coefficient k=0,68 m/h. The time of the vertical infiltration into the aquifer has been estimated at t=14,4 days. The investigations carried out during fertilization with the sludge have revealed an undoubted increase in the concentration of some ions as well as the increase in pH of the groundwater. The increase in the amount of some ions (e.g. N-NO3, SO4, Zn) as well as detergents indicates the possibility (as function of time) of reaching higher values than the ones permissible for drinking water. The phenomenon of the increase in the concentration of the particular ions will be accelerated after depletion of sorption of the soil in the unsaturated zone. The time can be estimated for not more than several years, taking into account a small area of the fertilized fields and high contents of “pollution” in the sludge (the total of the heavy metals reaches up to 1,5 g/kg)